An Econometric Forecasting Model for Foreign Trade: Evidence From Tunisia - Terzi, Chokri; Ammari, Anis El (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2018)
In this paper and without application because of the not availability of the data, the authors propose specific models in static and dynamic framework to analyze and forecast the evolution of the main components of the foreign trade of the Tunisian economy. For instance, they model and interpret the elasticities of imports and exports to changes in the prices and income. This approach thereby adds theoretical depth to a model that has a good forecasting performance. This paper is one among rare papers which focus on the modelling of the Tunisian foreign trade based on this approach.